Diastolic dysfunction in people with HIV without known cardiovascular risk factors in Western Kenya. Issue 1 (21st January 2022) - Woldu, Bethel; Temu, Tecla M; Kirui, Nicholas; Christopher, Bridgette; Ndege, Samson; Post, Wendy S; Kamano, Jemima; Bloomfield, Gerald S
Abstract : Objectives: Diastolic dysfunction (DD) has been reported to be highly prevalent in people living with HIV (PLWH) on antiretroviral therapy (ART) leading to the hypothesis that it may be an early marker of myocardial disease. Our objective was to evaluate the prevalence of DD in people living with human immunodeficiency virus without known history of diabetes or hypertension in Western Kenya. Methods: In this cross-sectional study in western Kenya, 110 PLWH on ART and without known diabetes or hypertension were matched for age ±5 years and sex to HIV-uninfected controls. Study participants underwent a comprehensive two-dimensional echocardiogram and laboratory testing. Results: The mean (SD) age in the HIV-positive group was 42.9 (8.6) years compared with 42.1 (12.9) years in the HIV-uninfected group. Mean (SD) CD4 +T cell count for the HIV-positive group was 557 (220) cells/ml. Mean systolic and diastolic blood pressures were within the normal range and comparable between the two groups. Mean body mass index was 25.2 (5.4) kg/m 2 and 26.3 (5.4) kg/m 2 in HIV-positive and uninfected participants, respectively. There was only 1 (0.9 %) case of DD in each group. Despite low prevalence of DD, PLWH had 5.76 g/m 2 higher left ventricular mass index (p=0.01) and 2.77 mL/m 2 larger left atrial volume (p=0.02) compared with the HIV-negative group after adjusting for risk factors associated with DD. Conclusion: Contrary to prior reports, DD in PLWH was low. Environmental and cardiovascular disease risk factors such as diabetes and hypertension may be significant modifiers for development and progression of DD in PLWH.